(untitled) (KULT_online, 2024)
In his recent volume, sociologist Bryan Turner attempts to formulate a theory of catastrophe based on observations regarding historical events. Beginning with a quote from Walter Benjamin, Turner’s book covers concepts like Ulrich Beck’s “risk society” and Zygmunt Bauman’s “liquid modernity,” in addition to occurrences like the Enlightenment, the Black Plague, colonialism, war, and utopian thought. Ambitious from the outset, the volume contains shortcomings and contributes little to the catastrophe discourse; indeed, a theory of catastrophe never arrives.